Development of glass optical fibers based on fluoride-phosphate for deep-UV optical transmission - Galleani, Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The development of new optical fibers capable to operate in the deep-ultraviolet (DUV, 200-300 nm) and the vacuum-ultraviolet (VUV, 120-200 nm) would benefit to laser technologies, microlithography techniques (increased spatial resolution) and elemental chemical sensing applications (phosphorous and sulfur sensing in agriculture). The only well-established UV-transmitting fiber existing to date consists in high- OH/fluorine doped silica glass core/clad fibers. However, the utilization of such fibers is limited by solarisation effect that degrades the UV-light transmission with long time exposition. Mixed fluoride-phosphate (FP) glasses with ultra-low content of impurities can be VUV- and/or DUV-transmitting materials, offering thus an alternative to the commercialized high-OH/fluorine doped silica fibers. These glasses are produced by mixing fluorides and polyphosphates to combine their properties as excellent glass-forming ability, low refractive index and broad optical transmission windows ranging from ~160 to 4000 nm. Also, when doped with trivalent rare-earth (RE) ions, the low phonon fluorine environment is favorable for RE high quantum efficiencies, making then suitable for photonic application in the form of fiber and/or bulk glass. Firstly, highly pure FP glasses were prepared and utilized to fabricate step-index optical fibers, by a modified crucible technique. In a first step, the bulk glasses were studied to be highly transparent in the VUV region, down to 160 nm, and the characteristics temperatures, viscosity around softening point were characterized. Then, the fibers were fabricated by the crucible technique, drawing the as-made core-cladding preforms in a silica crucible assembly. While uncontrolled crystallization was observed during the fiber drawing by the conventional method, drawing from a fused silica crucible showed to be suitable to obtain crystal-free FP glass fibers. Additionally, the cut-back method was employed to measure the optical attenuation on the FP step-index and single index glass fibers. The second part of this thesis involves the network structural investigation of a series of FP glasses with different fluoride/phosphate ratio. Raman and multinuclear solid-state nuclear magnetic resonance (NMR) spectroscopies were used to study the polyphosphate network transformation for the different fluoride/phosphate ratios. In the next step 27Al/31P ix double resonance techniques were used to quantify the average number of P-O-Al linkages in the glasses and the local environment of fluoride species were also determined. Then, the glasses were doped with RE ions and the local environment was characterized by electron paramagnetic resonance (EPR) spectroscopy of Yb3+ ions probe and by photoluminescence experiments on Eu3+ dopant ions. The luminescence properties were correlated with the structural transformation as a function of composition. Lastly, due to the high UV tansparency of the FP glasses, we prepared FP glasses doped with Gd3+, Tm3+, and Yb3+ ions as a potential candidate for fabrication of UV fiber lasers. The photoluminescence properties under 980 nm diode laser excitation were studied, and the effect of fluoride/phosphate ratio in the glasses in the Gd3+ UV upconversion (UC) emission were verified. The effect of Gd3+ content in the UV UC emission was also studied. Then, by using 45Sc/31P double resonance technique, utilizing scandium as a diamagnetic mimic for the luminescent RE species, the ligand distribution surrounding the RE ions were quantified, and the efficiency of the Gd3+ emission, compared to the Tm3+ ions with structure was done.

O desenvolvimento de novas fibras ópticas capazes de operar na região do ultravioleta profundo (200-300 nm) e de vácuo (120-200 nm) beneficiariam aplicações em tecnologias a laser, técnicas de microlitografia (maior resolução espacial) e detecção química elementar (detecção de fósforo e enxofre na agricultura). A única fibra de transmissão UV bem estabelecida existente até o momento consiste em fibras núcleo-casca de vidro de sílica dopado com OH/flúor. No entanto, a utilização de tais fibras é limitada pelo efeito de solarização que degrada a transmissão da luz UV apos exposição prolongada. Os vidros mistos fluoreto-fosfato com baixas quantidades de impurezas, são materiais transmissores de luz UV-profundo e vácuo, oferecendo assim uma alternativa frente as fibras de silica utilizadas hoje. Estes vidros são produzidos pela mistura de fluoretos e polifosfatos com propriedades combinadas de ambos como, excelente capacidade de formação vítrea, baixo índice de refração e ampla janela de transmissão (~ 160 a 4000 nm). Além disso, quando dopados com íons terras-raras trivalentes, o ambiente de baixa energia de fonon dos fluoretos é favorável para emissões dos TRs com alta eficiência quântica, tornando-os então adequados para aplicações na área da fotônica na forma de fibra e/ou bulk. Portanto, em primeiro lugar, foram preparados vidros FP altamente puros e utilizados para fabricação de fibras ópticas de índice-degrau, pela técnica do cadinho. Na primeira etapa, os vidros na forma de bulk foram estudados para serem altamente transparentes na região ultravioleta de vácuo, até 160 nm, e suas temperaturas características e a viscosidade em torno do ponto de amolecimento foram caracterizadas. Em seguida, as fibras foram fabricadas pela técnica do cadinho, preparando as preformas núcleo-casca em um conjunto de cadinho de sílica. Embora a cristalização não controlada tenha sido observada durante o puxamento das fibras pelo método convencional, o puxamento pelo método do cadinho mostrou-se adequado para obtenção de fibras de vidro FP sem cristalização. Além disso, a atenuação óptica nna fibra obtida foi medida na região UV. A segunda parte desta tese envolveu a investigação estrutural de uma série de vidros FP com diferentes razoes fluoreto/fosfato. As espectroscopias RMN do estado solido e Raman foram utilizadas para estudar a transformação da rede de polifosfatos para as xi diferentes razoes fluoreto/fosfato. Na etapa seguinte, utilizaram-se técnicas de dupla ressonância do 27Al/31P para quantificar o número médio de ligações P-O-Al nos vidros e o ambiente local das espécies fluoreto também foi determinado. Em seguida, os vidros foram dopados com íons TRs e o ambiente local foi caracterizado por espectroscopia EPR da sonda de íons
Desenvolvimento de fibras ópticas à base de vidros fluoreto-fosfato para transmissão óptica no UV-profundo
Keywords: Vidros; Fibras ópticas; Ressonância magnética nuclear